O zoológico do CIGS e o ensino de ciências na Amazônia - Lobo, Huanderson Barroso (2017)
Throughout its existence, zoos have been rebuilding their functions and today play a fundamental role in the construction of a scientific culture, also forming as an institutionalized non-formal space for the propagation of science. The objective of this research was to understand the possibilities of teaching science from the resources of fauna and flora existing in the Zoo of CIGS, based on a phenomenological perspective of science teaching. The research presents a qualitative approach of descriptive and analytical nature, the phenomenological method was used to describe the experiences of observations and interpretations. As techniques and instruments of the research, the following were used: bibliographical readings, field visits, participant observation and analysis of institutional documents. The theoretical foundation was based on the works of Merleau-Ponty (1999), Astolfi (1997, 1998) and Bachelard (1996). This dissertation presents three chapters. The first one, brings a reflection and analyzes, from a phenomenological approach, the students' understanding of the production of science teaching activities. The second describes the natural and physical resources of the CIGS Zoo, based on the phenomenological understanding, highlighting the characteristics and educational potential that this space offers, as well as discussing and presenting data on problems that affect these resources, such as deforestation, extinction of species and loss of biodiversity. In the last chapter, the development of a didactic sequence carried out with the students of elementary school II, begun in the school and completed in the zoo of the CIGS. After the development of the activities we perceive the rectification of several concepts, in this way we consider that the motor activities contribute in the process of knowledge construction